Orienting of attention and Parkinson's disease: tactile inhibition of return and response inhibition. - Poliakoff, E; O'Boyle, D; Moore, A; McGlone, F; Cody, F; Spence, C (2003)
There is growing evidence for cognitive impairments in Parkinson's disease (PD), including in the orienting of attention and inhibition of return (IOR). IOR refers to the slowing of a response to a target stimulus presented in the same location as a previous stimulus. While some researchers have reported normal levels of visual IOR in PD patients using cue-target tasks, others have reported significant reductions in IOR in this patient group. However, the inhibitory effects observed in cue-target tasks may reflect non-ocular response inhibition associated with withholding a response from the cue stimulus, rather than attentional or oculomotor processes. Many researchers working with normal participants have circumvented this confound by using a target-target task, in which a response is made to all peripheral stimuli. Here, we compared IOR measured in cue-target and target-target tasks, using tactile rather than visual stimuli. Both the PD and the control groups exhibited significant inhibitory effects in the cue-target task, but only the control group exhibited significant IOR in the target-target task. Our results demonstrate a reduction, or elimination, of IOR in PD and this change may have been underestimated in previous studies, in which methodologically flawed cue-target tasks were used. This reduction in IOR may reflect impaired inhibitory processes or hyper-reflexive orienting in parkinsonian patients.